Diversity and Selection of Cotton Germplasm Based on Morpho-Agronomic Character Performance - Rahman Side, Taufiq Hidayat; Yamin, Mayasari; Mulyani, Sri; Qadri, Sri Nur; Ayunawati, Luthfi; Aji, Agung Pangestu (HAYATI Journal of Biosciences, 2025)
Cotton is a plant that produces natural fibers of high economic value. Developing a new superior variety of cotton is expected to support fiber demand in Indonesia. The purpose of this study was to determine the diversity of morpho-agronomic characters and obtain secondary characters and cotton accessions that support the development of a new superior cotton variety. The genetic material used was 266 cotton accessions from the ISFCRI germplasm collection. Primary data of the 16 quantitative morphological characters were observed and analyzed using descriptive data, correlation analysis, path analysis, scatterplot, and grouping. The fiber length character has a very low diversity with a value of 0.01, and the plant height character has the highest variance, which is 637.42. The lint percentage with a variance value of 9.37 is influenced by duplicate epistasis genes and controlled by many genes. The fiber's fineness character has a positive and very significant correlation value to the character of the lint percentage. It has fairly high direct and total effect values of 0.156 and 0.134, respectively. Four accession groups can potentially support developing a new superior variety; accession CEA N 268, CEDIX, or L21999-10-71 can be used as the parent of new superior cotton varieties.